Caring for Caregivers of High-Needs Older Persons - Natalie Warrick, Allie Peckham, Jillian Watkins, Marija Padjen and A. Paul Williams (Healthcare Quarterly, 2014)
The Caregiver Framework for Seniors Project (CFSP) is led by the Alzheimer Society of Toronto in partnership with the Toronto Central Community Care Access Centre and six community support service agencies. This ground-breaking initiative aims to increase caregiver resiliency and capacity to continue to provide care through a platform of supports. In the CFSP, care coordinators negotiate flexible support packages in consultation with caregivers to meet their self-reported needs and the needs of care recipients. This paper presents the findings from a multi-stage, mixed-methods formative evaluation of the CFSP.
Keywords: family caregiving, patient centred care, care for the elderly, caregiver stress